Harmonizing Knowledge Frontiers: TGKH. Muhammad Zainuddin Abdul Madjid's Innovative Integration Model at Nahdlatul Wathan Educational Institute - Khairi Khairi; Fahrurrozi Fahrurrozi; Muhammad Thohri; Prosmala Hadisaputra (AL-ISHLAH: Jurnal Pendidikan, 2024)
The paper examines the scientific integration through the lens of TGKH. Muhammad Zainuddin Abdul Madjid. This study aims to explore the scientific integration model of TGKH Muhammad Zainuddin Abdul Madjid in the Nahdlatul Wathan educational institution. The study was conducted at the Shaykh Zainuddin Islamic Boarding School, the management center for the Nahdlatul Wathan organization. This study is a qualitative-descriptive study. Data were collected through interviews, observation, and documentation techniques, while data were analyzed using a sociological-historical approach. The analytical procedure used is the analysis procedure of Miles and Huberman. In this study, the scientific integration model proposed by TGKH Muhammad Zainuddin Abdul Madjid (Mawlana Shaykh) consists of three main components: 1) the integration of scientific knowledge with Islamic science and the Nahdlatul Wathan (Ke-NW-an) curriculum; 2) the institutional integration between Ma'had Darul Qur'an wal Hadith and higher education; 3) the integration of Islamic religious subjects with scientific disciplines. The findings of this study provide a foundation for policymakers to formulate more extensive and unified education strategies. This emphasises the significance of keeping an equilibrium between religious and scientific knowledge within the curriculum.